Screening of important viruses in felines and molecular characterization of parvovirus isolate from a tiger in Malaysia - Ahmad Nadzri, Nur Farahiyah (2018)
Animals under the family Felidae both domesticated and in the wild are potentially harbouring viruses of importance to other animals and humans. Canine Parvovirus (CPV) is a single stranded DNA virus which known to cause severe disease in younger unvaccinated animals. Despite the widespread vaccination of domestic carnivores, CPV is still an important pathogen of domestic and wild carnivores. In addition, CPV able to infect a wide range of feline hosts, hence, allowing it to infect both cats and dogs. Although, CPV is well studied in canine, limited information is available on it occurrence in various species of felids found in Malaysia. This study investigated detection of viruses of potential importance in different species of felines namely leopards, feral cats and tigers in Malaysia based on virus isolation in Crandell Rees feline kidney (CRFK) cells, polymerase chain reaction (PCR) using gene-specific primers and sequence analysis. From a total of 36 samples collected, 11 samples showed cytopathic effect in cell culture and were subjected to PCR using specific primers for feline herpesvirus (FHV), feline calicivirus (FCV), canine distemper virus (CDV) and CPV. However, only one sample from a tiger was detected positive for canine parvovirus (CPV). The entire viral genome of the sample CPV/MY/MT4 was amplified by PCR for sequencing using Sanger sequencing approach. Genome sequencing of the isolate revealed substitution of amino acid which characterized the isolate as variant CPV namely new CPV-2a with a characteristic’s amino acid substitution at position 297 of VP2 gene from serine to alanine (297-Ser-Ala). Additionally, at amino acid residue 426, isolate CPV/MY/MT4 have amino acid substitution aspartic acid to asparagine (Asp-426-Asn), which also revealed that the isolate has specific amino acid for CPV-2a. In addition, CPV/MY/MT4 was found to be phylogenetically close to new CPV-2a strain from other countries namely USA and Japan. The rest of the other new CPV-2a strains had distinct lineage but shared molecular relationship with the isolate CPV/MY/MT4. In conclusion, genome sequencing of the isolated CPV provided valuable information of the molecular characteristic of the isolate for further study on the importance of this virus in tigers and species of felids.